Analysis of Independent Curriculum Development at Elementary School Level: A Descriptive Qualitative Approach at Sdn 02 Tanjungjaya Banjarwangi Garut - Zaki Bahrul Ulum; Muhammad Nasir (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
The evolution of the Merdeka Curriculum within primary education has emerged as a pivotal topic in the effort to cultivate a more adaptable, contextualized, and student-centric educational environment. This inquiry intends to examine the progression of the Merdeka Curriculum at SDN 02 Tanjungjaya Banjarwangi Garut, focusing specifically on curriculum design, pedagogical execution, evaluation methods, the integration of the Pancasila Student Profile, and the institutional obstacles encountered throughout its adoption. Utilizing a descriptive qualitative design, data gathered for this study were compiled via semi-structured interviews, direct observations, and archival reviews involving the school headmaster, teaching staff, and official institutional documents. The outcomes demonstrate that curriculum advancement at SDN 02 Tanjungjaya was realized by modifying the school’s operational curriculum, constructing lesson plans aligned with targeted learning outcomes, introducing versatile instructional methods, and organizing project-based activities for the Pancasila Student Profile tailored to the local environment. Nonetheless, several bottlenecks persist, such as disparate teacher comprehension, inadequate educational resources, unreadiness for formative assessments, and a deficiency in sustainable mentoring. This paper deduces that optimizing the Merdeka Curriculum in primary schools necessitates responsive institutional leadership, robust peer collaboration among educators, active parental engagement, and continuous professional development for teachers to ensure the curriculum positively reshapes educational quality.